Introduction to liquid argon time projection chamber operation and calibration methods - Ruhnow, Kelley (Kansas State University, 2022)
Neutrinos are an interesting type of particle that could provide insight to unanswered questions such as the imbalance of matter and antimatter in the universe. However, they’re difficult, if not impossible, to detect directly. Modern particle physics experiments build detectors called Liquid Argon Time Projection Chambers (LArTPCs) that detect the products of neutrino interactions. Due to various processes that take place within the detector, the data that comes out of these detectors ends up being distorted; various calibration techniques are necessary to ensure that the data is accurate and undistorted. All of these aspects of LArTPCs are complex on their own, let alone when they are all occurring in tandem. In this paper I will describe the basic principles behind LArTPC operation and data collection, and the calibration techniques that are carried out in the detector. I will also provide a brief comparison of various data from several of the more recent LArTPC experiments. This description of basic principles may prove useful to people who are familiarizing themselves with LArTPC experiments as part of their research endeavors.
Keywords: High energy physics; Neutrinos; Time projection chamber; Liquid argon